Profile of the Need for STEM Teaching Materials in Science Learning in Vocational Schools - Susilawati, Aay; Rochintaniawati, Diana; Hasanah, Lilik; Kustiawan, Iwan; Rustaman, Nuryani; Kaniawati, Ida (IJIS Edu : Indonesian Journal of Integrated Science Education, 2023)
Science education in vocational schools has undergone several changes in subject characteristics. Scienceteachers need to understand these characteristics to facilitate the delivery and implementation of learning inthe classroom. Therefore, the purpose of this article is to describe the requirements profile of needs forSTEM teaching materials in science learning at vocational schools. The research methods used aredescriptive and qualitative through field observations (field studies) derived from professional research inthe form of curriculum documents, lesson plans, learning videos, and analysis of six science textbooks invocational school. The results of a curriculum analysis from document, videos and textbooks on theavailability of project-based STEM components in learning equipment plans and existing materials are stillinadequate to support the life skills of 21st century professional students, and the following curriculumrequirements are: Not yet supported. So, in future research need integration, project-based, and underlyingskills according to competency skills in vocational school.